The metabolic repression effect of carbon-ion radiotherapy in synchronous hormone-sensitive oligometastatic prostate cancer - Zhang, Zhenshan; Pei, Yulei; Hu, Wei; Xue, Yushan; Ning, Renli; Guo, Xiaomao; Sun, Yun; Zhang, Qing (Frontiers in Endocrinology, 2023)
Abstract Background: Metastatic prostate cancer (PCa) poses a significant public health concern. While radiation therapy (RT) is commonly utilized in the treatment of synchronous oligometastatic hormone sensitive prostate cancer (OM-HSPC), the occurrence of biochemical recurrence still remains. To deepen our understanding and optimize the outcome of OM-HSPC, we conducted this study to investigate the characteristics of PCa progression and explore potential synergistic mechanisms involving carbon-ion radiotherapy (CIRT) and neoadjuvant androgen deprivation treatment (naADT) in OM-HSPC. Methods: Metabolomic analysis was conducted with 72 urinary samples (at different timepoints) from 33 Patients (T2-3N0M0-1b) and 18 healthy volunteers by using liquid chromatography-tandem mass spectrometry (LC-MS/MS). MetaboAnalyst website and R software were employed for metabolomic analysis and visualization (using the criteria of p value < 0.05 and |FC|>1.5,). The impact of CIRT on metabolism were further verified and explored through in vitro and in vivo experiments. Results: We found that most metabolites (223 out of 233) were upregulated in treatment-naïve PCa samples compared to healthy samples. After naADT, 60 core risk metabolites were still significantly related to PCa’ progression, and the glutamine level which was significantly higher in OM-HSPC compared to other groups. Remarkably, after CIRT treatment, the glutamine levels in OM-HSPC were significantly reduced to the level of healthy samples. Experiments further confirmed CIRT's ability to suppress glutamine levels in PCa tumors and its potential enhancement with glutamine deprivation intervention. Conclusion: CIRT with naADT might synergistically inhibit HS-OMPC development, progression and even the ADT resistance through glutamine metabolism repression, moreover, the glutamine metabolism might be a novel target to further improved the efficacy of CIRT. Keywords: Carbon ion radiotherapy, metastatic prostate cancer, metabolomics, hormone treatment.